Duvalo "Volcano" (North Macedonia): A Purely Tectonic‐Related CO2 Degassing System. (31st March 2022) - Li Vigni, L.; Cardellini, C.; Temovski, M.; Ionescu, A.; Molnár, K.; Palcsu, L.; Gagliano, A. L.; Cappuzzo, S.; D'Alessandro, W.
Abstract: Duvalo "volcano" is a site of anomalous geogenic degassing close to Ohrid (North Macedonia) not related to volcanic activity, despite its name. CO2 flux measurements made with the accumulation chamber (321 sites over ∼50, 000 m 2 ) showed fluxes up to nearly 60, 000 g m −2  d −1, sustaining a total output of ∼67 t d −1 . Soil gas samples were taken at 50 cm depth from sites with high CO2 fluxes and analyzed for their chemical and isotope composition. The gas is mainly composed by CO2 (>90%) with significant concentrations of H2 S (up to 0.55%) and CH4 (up to 0.32%). The isotope compositions of He ( R / R A 0.10) and of CO2 (δ 13 C ∼ 0‰) exclude significant mantle contribution, while δ 13 C‐CH4 (∼−35‰) and δ 2 H‐CH4 (∼−170‰) suggest a thermogenic origin for CH4 . The area is characterized by intense seismic activity and Duvalo corresponds to an active tectonic structure bordering the Ohrid graben. The production of H2 S within the stratigraphic sequence may be explained by thermochemical reduction of sulfate. The uprising H2 S is partially oxidized to sulfuric acid that, reacting with carbonate rocks, releases CO2 . The tectonic structure of the area favors fluid circulation, sustaining H2 S production and oxidation, CO2 production and allowing the escape of the gases to the atmosphere. In the end, Duvalo represents a tectonic‐related CO2 degassing area whose gases originate mostly, if not exclusively, in the shallowest part of the crust (<10 km). This finding highlights that even systems with trivial mantle contribution may sustain intense CO2 degassing (>1, 000 t km −2  d −1 ). Plain Language Summary: The carbon cycle is an important piece of the puzzle of the present climate change. While anthropogenic sources of atmospheric carbon are reasonably constrained, geological sources are much less. Among the latter, carbon release to the atmosphere in seismically active areas, though known from decades, is less studied. Here we estimate the total emission of carbon dioxide from Duvalo, an area near Ohrid (North Macedonia). The obtained value (67 metric tons per day) is comparable with some active volcanic areas in the region. Although local inhabitants call this area Duvalo volcano, no recent volcanic activity is recognized here. The composition of the gas released by this system seems also to rule out geothermal activity or deep contributions from the Earth's mantle. This study shows that natural degassing systems with relatively shallow crustal sources (few kilometers), may sustain intense gas emissions from the soil. Key Points: The total CO2 output from Duvalo "volcano" has been estimated for the first time Gas compositions rule out significant mantle contributions or recent volcanic activity while geothermal activity is improbable An active fault system favors indirect gas production and upflow to the Earth's surface